+0  
 
+1
138
2
avatar+321 

How to simplify the equation -3sqrt(5)/sqrt(15)

Davis  Mar 2, 2017

Best Answer 

 #1
avatar+5565 
+6

\(\frac{-3\sqrt{5}}{\sqrt{15}} \\ = \frac{-3\sqrt{5}(\sqrt{15})}{\sqrt{15}(\sqrt{15})} \\ = \frac{-3\sqrt{75}}{15} \\ = \frac{-3(5\sqrt{3})}{15} \\ = \frac{-15\sqrt{3}}{15} \\ = -\sqrt{3}\)

 

:)

hectictar  Mar 2, 2017
Sort: 

2+0 Answers

 #1
avatar+5565 
+6
Best Answer

\(\frac{-3\sqrt{5}}{\sqrt{15}} \\ = \frac{-3\sqrt{5}(\sqrt{15})}{\sqrt{15}(\sqrt{15})} \\ = \frac{-3\sqrt{75}}{15} \\ = \frac{-3(5\sqrt{3})}{15} \\ = \frac{-15\sqrt{3}}{15} \\ = -\sqrt{3}\)

 

:)

hectictar  Mar 2, 2017
 #2
avatar+321 
+5

Thx

Davis  Mar 2, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details